ANALISIS BIMBINGAN BELAJAR SISWA BERKESULITAN MEMBACA - Sonnia Neng Bagus; Wawan Syahiril Anwar; Yudhie Suchyadi (Universitas Pakuan, 2022)
ANALYSIS OF TUTORING STUDENTS HAVING DIFFICULTY READINGAnalysis of Student Guidance with Difficulty Reading. Qualitative research with a descriptive study approach. Thesis of Elementary School Teacher Education Study Program, Faculty of Teacher Training and Education, Pakuan University, Bogor, 2020. The objective is to describe the forms of learning difficulties to read, factors of reading difficulties and tutoring for students with reading difficulties. The subjects of this study were 3 students of class IIIA IIIB Cimayang State Elementary School 01. The research was carried out in the odd semester of the 2020-2021 school year. In collecting data, researchers used observation, interview and documentation methods. Researchers used credibility, transferability, dependability, and confirmability tests to obtain data validity. The results showed that the form of reading difficulty students could not distinguish letters that were almost the same shape, students did not recognize diphthong and digraphs, students stammered reading syllables, students could not read words, could not pronounce letters in one sentence and still spell letters. The factors that cause student reading difficulties are students lack of interest in reading, the family environment lack of parental attention to their children's learning activities at home, lack of enthusiasm for students in learning, teaching methods and media used by teachers when the teaching and learning process is inadequate does not vary, disturbances in health. Guidance for students having difficulty learning to read at SD Negeri Cimayang 01 is still not optimal. The role of the school in providing guidance for students with difficulty learning to read is also not optimal. In addition, the ability of students to have difficulty learning to read in overcoming their learning difficulties is still lacking.